2015
DOI: 10.6018/analesps.31.3.184221
|View full text |Cite
|
Sign up to set email alerts
|

The unidimensionality and overestimation of metacognitive awareness in children:validating the CATOM

Abstract: Título: Unidimensionalidad y sobreestimación de la conciencia metacognitiva en niños: Validación del CATOM. Resumen. Los niños normalmente tienen dificultades para informar sobre su funcionamiento metacognitivo, hecho que, con frecuencia, les lleva a sobrevalorarse en situaciones de aprendizaje. Por tanto, este estudio pretende comprender cómo los niños (n = 1029) informan sobre su funcionamiento metacognitivo y ofrece una primera aproximación a la medición de la conciencia metacognitiva (CM) en niños. Así, tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 71 publications
(70 reference statements)
3
4
0
Order By: Relevance
“…Specifically, there was an overestimation of how they planned, performed, and monitored, and reflected and evaluated their work. These results are in line with those of other studies (Ferreira et al, 2015a). However, the present study focused on middle school students and did not contemplate a particular discipline.…”
Section: Discussionsupporting
confidence: 93%
“…Specifically, there was an overestimation of how they planned, performed, and monitored, and reflected and evaluated their work. These results are in line with those of other studies (Ferreira et al, 2015a). However, the present study focused on middle school students and did not contemplate a particular discipline.…”
Section: Discussionsupporting
confidence: 93%
“…), we observed that fifth grade students more frequently reported to be familiar with this strategy than sixth grade students. This is in accordance with findings that younger children's metacognitive self-reports are prone to overestimation (e.g., Ferreira, Simão, & da Silva, 2015). However, regardless of the underlying mechanism (i.e., utilization deficiency or overestimation), our findings complement results of previous studies in which reading strategy knowledge seemed to be more highly related with reading performance at higher grade levels (e.g., Kolić-Vehovec et al, 2014;van Kraayenoord & Schneider, 1999).…”
Section: Reading Strategy Knowledge and Reading Comprehensionsupporting
confidence: 80%
“…Moreover, the questioning approach applied in this study seems to be feasible to replicate in daily educational practices, promoting experiences where children are actively engaged in the learning process. The goal of such opportunities should help them to overcome obstacles and progressively learn to think about thinking – metacognitive awareness ( Ferreira et al., 2015 ; Marulis et al., 2016 ; Romera, 2003 ). Analyzing the IRT low-reliability levels, we advocate that those results were not due to the difficulty of the items.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, different types of measures were used in each phase seeking to capture SRL processes from a dynamic, cyclical, and multidimensional perspective. The specific measures considered the developmental characteristics of the children (Ferreira, Veiga Simão, & Silva, 2015;Lopes da Silva et al, 2004), such as their difficulty to speak about self-regulatory processes. Self-reported data was complemented by other sources, namely observation data and the product of the task, with a view to data triangulation.…”
Section: Methods 41 Participantsmentioning
confidence: 99%
See 1 more Smart Citation